A systematic review of the efficacy of a single dose artemisinin–naphthoquine in treating uncomplicated malaria - Naing, Cho (Malar J, 2015)
BACKGROUND: This study aimed to synthesize the existing evidence on the efficacy and safety of a single dose artemisinin–naphthoquine (ASNQ) for treatment of uncomplicated malaria in endemic countries. METHODS: A meta-analysis of randomized, controlled trials (RCT), assessing efficacy and safety of single dose ASNQ was carried out. Comparator drugs included artemether–lumefentrine (AL), chloroquine plus sulfadoxine-pyrimethamine (CQSP) and dihydroartemisinin–piperaquine (DHP). The efficacy and safety profile of non-comparator, single-arm studies on the single dose ASNQ was also assessed. The primary endpoint was efficacy defined as an absence of PCR-confirmed parasitaemia. The methodological quality of the included studies was assessed using the six domains for the risk of bias. RESULTS: Five RCTs and three single-arm studies were included in this review. As RCT studies did not compare the same anti-malarial drugs, it was difficult to do a pooled analysis. At day 28, a pooled analysis of two RCTs (n = 271) showed a comparable efficacy on PCR-confirmed parasitaemia between ASNQ and AL. Another RCT, which compared ASNQ and CQSP or ASNQ and DHP, also showed comparable efficacy. At day 42, one RCT comparing ASNQ and DHP and another RCT comparing ASNQ and AL reported comparable levels of efficacy. The proportion of parasite clearance was faster in the ASNQ groups than the comparators at day 1, and almost all parasites were cleared by day 3 in the ASNQ groups. CONCLUSIONS: The present review provides some evidence to support that there is similar efficacy and safety of the single dose ASNQ compared to other anti-malarial drugs in treating uncomplicated malaria. Larger, adequately powered, well-designed studies are recommended to substantiate the efficacy and safety in different populations and in different epidemiological settings. As the potential evolution of drug resistance is a great concern and this cannot be addressed in a short-term study, the use of single dose ASNQ needs further evaluation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-015-0919-5) contains supplementary material, which is available to authorized users.